Drug interaction between acetyltanshinone IIA and rapamycin in breast cancer cells - Wong, De Pin (2014)
Combination drug therapy is most widely used in breast cancer treatment. One of the key benefits of drug combination is the effect of synergism which provides mutual enhancement to the therapeutic effect. Developing in vitro drug combination study is essential for the development of new and effective combination regimens. In this project, the objective is to investigate the synergistic potential between two anti breast cancer agent, rapamycin and acetyltanshinone IIA (ATA) in breast cancer cells. MTT assay was performed to test for the growth inhibitory effect of individual drugs and their combinations. Drug combination studies for both non fixed and fixed constant ratio (1:6400) were conducted. Median drug effect analysis was performed using the software CompuSyn to determine the combination index value and the synergism between the drugs. Result indicated that drug combination between rapamycin and ATA resulted in increase in growth inhibitory effect in both non fixed and fixed constant ratio studies. Median drug effect analysis showed that there is strong level of synergism between rapamycin and ATA.